2015
DOI: 10.1111/evo.12730
|View full text |Cite
|
Sign up to set email alerts
|

Tempo and mode of climatic niche evolution in Primates

Abstract: Climatic niches have increasingly become a nexus in our understanding of a variety of ecological and evolutionary phenomena, from species distributions to latitudinal diversity gradients. Despite the increasing availability of comprehensive datasets on species ranges, phylogenetic histories, and georeferenced environmental conditions, studies on the evolution of climate niches have only begun to understand how niches evolve over evolutionary timescales. Here, using primates as a model system, we integrate rece… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
20
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 89 publications
4
20
1
Order By: Relevance
“…A previous analysis of the evolution of climatic niches found a greater number of diversification rate shifts among cercopithecids than any other primate clade (Duran and Pie 2015), suggesting that these shifts may be related to the presence of more variable climatic environments (e.g., montane regions, or ecosystems with monsoons). A previous analysis of the evolution of climatic niches found a greater number of diversification rate shifts among cercopithecids than any other primate clade (Duran and Pie 2015), suggesting that these shifts may be related to the presence of more variable climatic environments (e.g., montane regions, or ecosystems with monsoons).…”
Section: Discussionmentioning
confidence: 84%
“…A previous analysis of the evolution of climatic niches found a greater number of diversification rate shifts among cercopithecids than any other primate clade (Duran and Pie 2015), suggesting that these shifts may be related to the presence of more variable climatic environments (e.g., montane regions, or ecosystems with monsoons). A previous analysis of the evolution of climatic niches found a greater number of diversification rate shifts among cercopithecids than any other primate clade (Duran and Pie 2015), suggesting that these shifts may be related to the presence of more variable climatic environments (e.g., montane regions, or ecosystems with monsoons).…”
Section: Discussionmentioning
confidence: 84%
“…Our study represents, to our knowledge, the first one evaluating the existence of phylogenetic conservatism of climatic niches across the whole turtle clade. Climatic niche conservatism is a well‐studied subject in several vertebrate groups (Duran & Pie, ; Duran et al., ; Mcnyset, ; Peixoto et al., ; Peterson, ; Pie et al., ), but in turtles, it is still poorly explored. The few studies that have evaluated niche conservatism in this group found a mix of evidence for both divergence and conservatism, mainly in the biological invasions scenario (Liu et al., ; Rödder et al., ; Rodrigues, Coelho, & Diniz‐Filho, ; Rodrigues, Coelho, Varela, et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…Although evolutionary patterns of species' climatic niches have been recently evaluated in many taxa (Duran, Meyer, & Pie, 2013;Duran & Pie, 2015;Mcnyset, 2009;Peixoto, Villalobos, & Cianciaruso, 2017;Peterson, 2011;Pie, Campos, Meyer, & Duran, 2017), few studies have tested whether patterns of climatic niche evolution are related to other taxon traits. In mammals, for example, species occurring in the tropics, with small range sizes or with specialized diets have climatic niches that are more conserved than temperate, widely distributed and diet-generalist mammals (Cooper, Freckleton, & Jetz, 2011).…”
mentioning
confidence: 99%
“…We extracted the climatic data from all localities where species from the R. granulosa complex are reported to occur (Narvaes, 2003) using DIVA-GIS software. Given that temperature and precipitation data have very different scales (°C and mm) and that variances of precipitation data are much higher than temperature data, we opted to transform all climatic data using the z-score transformation (e.g., Duran & Pie, 2015) before constructing a climatic correlation matrix and extracting its principal components (PCs ; Table S4). We followed Desdevises et al (2003) to decide which PCo axes of the V/CV P-matrix dissimilarity were the dependent variables: only the ones for which there were significant correlations with any independent factor.…”
Section: Roles Of Phylogeny and Climate On P-matrix Dissimilaritymentioning
confidence: 99%